The Influence of Work Ethic and Organizational Culture on Employee Performance at PT XYZ - Edhu Enriadis Adilinga (Jurnal Syntax Transformation, 2023)
Human resources play an important role in achieving organizational or company goals. Rapid changes in the business environment and full of uncertainty make companies strive to produce high-performance employees. At PT XYZ throughout 2020-2022, there was a decrease in employee performance. The decline in performance is influenced by various factors, one of which is the internal factor of employees in the form of work ethic. In addition to work ethic, organizational culture factors also affect employee performance. This study aims to find out how about work ethic, organizational culture and performance at PT. XYZ Bandung, and how much influence work ethic and organizational culture have on employee performance at PT. XYZ Bandung either partially or simultaneously. The type of research used is quantitative, causal relationship with descriptive and verifiative approaches. The sample in this study was 139 respondents. Data collection techniques through the distribution of questionnaires, and data analysis using PLS structural equation modeling (SEM). The results showed that the work ethic of PT XYZ employees resulted in an average of 562.8 (81%) being in the high category. The organizational culture of PT XYZ resulted in an average of 530.8 (76.4%) being in the strong category. Hypothesis testing shows that partially and simultaneously work ethic and organizational culture have a significant effect on the performance of PT XYZ employees. The amount of influence of work ethic and organizational culture on employee performance is 0.588 or 58.8%. The results of the study provide an overview of the condition of PT XYZ Company. And the results of this research will provide a foundation in employee development at PT XYZ to be able to improve employee performance